2019
DOI: 10.1021/acs.chemrestox.8b00234
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gene × Environment Interactions on Silver Nanoparticle Toxicity in the Respiratory System

Abstract: Silver nanoparticles (AgNP) are used in multiple applications but primarily in the manufacturing of antimicrobial products. AgNP toxicity in the respiratory system is well characterized, but few in vitro or in vivo studies have evaluated the effects of interactions between host genetic and acquired factors or gene × environment interactions (G × E) on AgNP toxicity in the respiratory system. The primary goal of this article is to review host genetic and acquired factors identified across in vitro and in vivo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…We previously reviewed a Scoville et al study, which “treated 25 genotypes of male mice (including A/J, BALB/cJ, and C57BL6/J), and observed genotype effects on Ag mass associated in the lungs as well as AgNP‐induced T2 lung inflammation (marked by increased pro‐inflammatory cell secretion) compared to genetically‐matched vehicle controls, with BALB/cJ and SWR/J mice being the most differentially sensitive genotypes. The authors used RNA‐seq on lungs isolated from A/J, BALB/cJ, and C57BL6/J mice and observed an inverse relationship between AgNP‐induced T2 lung inflammation and expression of E3 ubiquitin‐protein ligase NEDD4‐like ( Nedd4l ), anoctamin 6 ( Ano6 ), and E3 ubiquitin‐protein ligase RNF220 ( Rnf220 ), which may function as candidate polymorphisms for AgNP‐induced T2 lung inflammation” (Nicholas et al, 2019; Scoville et al, 2017). We described Nedd4l as “a E3 ubiquitin ligase gene involved in ubiquitin protein ligase activity” and suggested that AgNP‐induced Nedd4l downregulation “may increase amiloride‐sensitive epithelial Na + channel (ENaC) activity and T2 lung inflammation” (Nicholas et al, 2019; Scoville et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reviewed a Scoville et al study, which “treated 25 genotypes of male mice (including A/J, BALB/cJ, and C57BL6/J), and observed genotype effects on Ag mass associated in the lungs as well as AgNP‐induced T2 lung inflammation (marked by increased pro‐inflammatory cell secretion) compared to genetically‐matched vehicle controls, with BALB/cJ and SWR/J mice being the most differentially sensitive genotypes. The authors used RNA‐seq on lungs isolated from A/J, BALB/cJ, and C57BL6/J mice and observed an inverse relationship between AgNP‐induced T2 lung inflammation and expression of E3 ubiquitin‐protein ligase NEDD4‐like ( Nedd4l ), anoctamin 6 ( Ano6 ), and E3 ubiquitin‐protein ligase RNF220 ( Rnf220 ), which may function as candidate polymorphisms for AgNP‐induced T2 lung inflammation” (Nicholas et al, 2019; Scoville et al, 2017). We described Nedd4l as “a E3 ubiquitin ligase gene involved in ubiquitin protein ligase activity” and suggested that AgNP‐induced Nedd4l downregulation “may increase amiloride‐sensitive epithelial Na + channel (ENaC) activity and T2 lung inflammation” (Nicholas et al, 2019; Scoville et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The authors used RNA‐seq on lungs isolated from A/J, BALB/cJ, and C57BL6/J mice and observed an inverse relationship between AgNP‐induced T2 lung inflammation and expression of E3 ubiquitin‐protein ligase NEDD4‐like ( Nedd4l ), anoctamin 6 ( Ano6 ), and E3 ubiquitin‐protein ligase RNF220 ( Rnf220 ), which may function as candidate polymorphisms for AgNP‐induced T2 lung inflammation” (Nicholas et al, 2019; Scoville et al, 2017). We described Nedd4l as “a E3 ubiquitin ligase gene involved in ubiquitin protein ligase activity” and suggested that AgNP‐induced Nedd4l downregulation “may increase amiloride‐sensitive epithelial Na + channel (ENaC) activity and T2 lung inflammation” (Nicholas et al, 2019; Scoville et al, 2017). We also described Ano6 as a “small‐conductance calcium‐activated nonselective cation channel gene involved in calcium‐dependent exposure of phosphatidylserine on the cell surface”, and posited that AgNP‐induced Ano6 downregulation “may impair ion transport, increase airway surface fluid volume and viscosity, as well as apoptosis, phagocytosis, and T2 lung inflammation and/or mast cell degranulation via the phosphatidylserine signaling pathway” (Nicholas et al, 2019; Scoville et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations